Impacto do estilo de vida fisicamente ativo na variabilidade da frequência cardíaca de mulheres com histórico familiar de hipertensão e diabetes - Zaffalon Júnior, José Robertto (2018)
Subjects with a family history of hypertension (SAH) and Type 2 Diabetes Mellitus (DM2) presented early impairment in heart rate variability (HRV) when compared to those without family history. Despite previous studies reporting the benefits of physical exercise in hypertensive and diabetic subjects, the benefits of a physically active lifestyle in subjects with family history SAH and DM2, especially among young women, have not been fully evaluated. Therefore, the aim of this thesis was to analyze metabolic, hemodynamic and autonomic parameters at rest and in response to sympathetic stimulation in sedentary and physically active women with family history of SAH, DM2 or SAH+DM2. We performed a cross-sectional study with 105 women (age: 18 to 30 years). We evaluated: family history of SAH/DM2; level of physical activity; blood pressure; glycemia; HRV in the time and frequency domain by recording the R-R intervals. For better analysis, the thesis was divided in four studies. In the sStudy 1 we analyzed the quality of life and hemodynamic and autonomic parameters at rest and in response to a mental stress test of sedentary (SW=48) and active (AW=48) young women. The results provided evidence that sedentary lifestyles impaired autonomic cardiac modulation both at rest and in response to physiological stress and worsed quality of life. In the Study 2 we analyzed the HRV in offspring: of normotensive and normoglycemic (NND, n=14), of hypertensive (HD, n=13), of diabetic (DD, n=11), and of diabetic and hypertensive (DFD, n=11). The results showed that the family history of SAH and/or DM2 induced impairment in HRV before clinical cardiovascular or glycemic alterations. In the Study 3 we analyzed the impact of lifestyle on the autonomic cardiac modulation in women with a family history of DM2. We compared offspring of: normoglycemic sedentary (SDN, n = 14), diabetic sedentary (DSD, n=11) and diabetic active (DAD, n = 14). We demonstrated that physically active lifestyles improve cardiac autonomic modulation in diabetic offspring. In the Study 4 we evaluated the influence of the family history of hypertension associated to DM2 on HRV at rest and in response to a mental stress test. We evaluated sedentary offspring of normotensive and normoglycemic (SDNN, n=13), sedentary and active offspring of hypertensive (SHD, n=13 and SAH, n=14), and sedentary and active offspring of hypertensive and diabetic (SHD, n=11 and AHD, n=14). We showed that physically active lifestyles induced improvement on cardiac autonomic modulation of women with a family history of SAH, but that the association with the family history of DM2 is responsible for attenuation of these benefits, especially in response to a mental stress test. In summary, our results demonstrated impairment on HRV in women with family history of SAH and DM2, highlight the importance of a physically active lifestyle in the prevention of early autonomic dysfunctions associated with the development of SAH and DM2 in genetically predisposed women, and also reinforced the HRV analysis as a possible early marker of cardiovascular risk in this population.